1992
DOI: 10.1111/j.1440-1681.1992.tb00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Handling of Endogenous Lithium in Experimental Diabetes Mellitus in the Rat

Abstract: 1. The usefulness of determining the renal handling of endogenous lithium as a marker of proximal tubular sodium reabsorption was assessed in streptozotocin induced diabetes mellitus in the Sprague-Dawley rat. 2. The clearance and fractional excretion of lithium were determined before and following the development of diabetes mellitus, and compared with measurements of proximal tubular reabsorption made directly using micropuncture techniques. Endogenous lithium was measured in order to avoid the toxic tubular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…A quantitative comparison of our results with these experimental data is difficult, because GFR and plasma glucose concentrations vary widely in these studies and the micropuncture site is not precisely identified. Nonetheless, our model predictions agree qualitatively with the observed increase in the fractional reabsorption of water and sodium (diabetic vs. normal rat proximal tubule) (34,33,40,43,45).…”
Section: Metabolic Efficiency Of the Proximal Tubule In Diabetic Ratssupporting
confidence: 78%
“…A quantitative comparison of our results with these experimental data is difficult, because GFR and plasma glucose concentrations vary widely in these studies and the micropuncture site is not precisely identified. Nonetheless, our model predictions agree qualitatively with the observed increase in the fractional reabsorption of water and sodium (diabetic vs. normal rat proximal tubule) (34,33,40,43,45).…”
Section: Metabolic Efficiency Of the Proximal Tubule In Diabetic Ratssupporting
confidence: 78%
“…The central tenets of the C Li approach are that lithium is reabsorbed in the proximal tubule in direct proportion to sodium and water but is not reabsorbed in the loop of Henle and the distal nephron. Micropuncture studies in rodents indicate that the C Li approach is less accurate in some disease settings, including T1DM (Pollock & Field, ), but nevertheless it remains a valuable qualitative marker of proximal tubule function (Thomsen & Shirley, ). Our data clearly show that C Li increases with BP to a similar extent in both T1DM and non‐diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Increased Na/H antiport activity was also docu mented in leukocytes from IDDM with albuminuria [22], Ng et al [22] observed that the elevated antiport activity in leukocytes is reversed by incubation with staurosporine, a protein kinase inhibitor, suggesting that protein kinase ac tivity (including PKC) in diabetic subjects may be higher; as staurosporine is not completely specific for PKC, other ki nases may also be involved. On the other hand, micropunc ture and microperfusion experiments have demonstrated that proximal tubular Na reabsorption is increased in dia betes meliitus [23,24]. It is possible that, similarly to blood cells, the renal Na /H countertransport could be activated, so causing the increment in tubular acidification and Na Values are means ± SE; n = number of measurements/'number o f tubules/number of rats.…”
Section: Discussionmentioning
confidence: 99%